Bowling Tourney to tighten the ties between UMP and Media - Siti Sarah, Mohamad Rajimi (2017)
A total of 150 participate in bowling tournament with media practitioners organized by Universiti Malaysia Pahang together with Pahang Media Club and UMP Advanced Education. Tournament was held at Mega Lane Kuantan and was attended by UMP Vice Chancellor, Prof. Dato’ Dr. Daing Nasir Ibrahim, Pahang Media Club President, Dato Nik Naizi Hussin, UMP Advanced Education Chief Executive Officer, Mohamad Rozi Hassan, Deputy Vice Chancellor (Student Affairs & Alumni) Prof. Dato’ Dr Yuserrie Zainuddin and UMP Registrar, Abd. Hamid Majid.